Perdas quali-quantitativas na colheita mecanizada de sementes de amendoim (Arachis hypogaea L.) - Barrozo, Leandra Matos [UNESP] (2009)
The experiment was carried out in the experimental FARM and in the Analysis and in the Phytopatology Laboratories belonging to College of Agriculture, São Paulo State University, Campus of Jaboticabal. The objective of this research was to quantify the losses of peanut crop harvesting and, also the qualitative, it was used a cultivar Runner IAC 886, and was analyzed the effect of the groundnut digger and the harvesting combine speeds. Were used two groundnut digger speeds (4.3 and 5.0 km h-1) and three harvesting combine speeds (3.5; 4.6 and 6.2 km h-1). In the digging process were evaluated the visible losses (PVA), the invisible losses (PIA), total losses groundnut digger (PTA), total visible losses (PVT), total losses in the crop (PTC), design of piles, distribution of straws and the real production. To the physiological quality were used the germination percentage (in sand and paper), first germination count, speed of emergence, seedling dry matter, accelerated aging, electrical conductivity, seedling emergence at field conditions and tetrazolium. For the statistical analysis it was used a completely randomized design consisting of two groundnut digger speed. In the combined harvesting was used a randomized block design in a split plot scheme. The plots were composed by two digger speeds and the split split plot by three combine harvesting speeds. The physiological seed quality were analized by the Shapiro-Will test and after were submitted to the analys of variance together with the sanity data, and the means compared by the Tukey test at 5% level of probability. The maximum and minimum speeds didn't influence in the qualitatife and quantitative losses of the peanut seeds.